2016
DOI: 10.5424/fs/2016251-07538
|View full text |Cite
|
Sign up to set email alerts
|

Mountain cloud forest and grown-shade coffee plantations: A comparison of tree biodiversity in central Veracruz, Mexico

Abstract: Aim of study: The objective of this work is to compare tree diversity and richness among one grown-shade coffee plantation (CAE) and two sites of montane cloud forests, one preserved (MCF1) and other perturbed (MCF2). We also develop an analysis of the importance of coffee plantations as a refuge of tree species, holding a potential role for conservation.Area of study: Our study area is the coffee region of Coatepec-Xico, in the state of Veracruz, Mexico. Material and Methods:We compiled a list of all tree spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 26 publications
(22 reference statements)
0
7
1
5
Order By: Relevance
“…Both studies identified Clethra mexicana, Liquidambar styraciflua, Quercus germana and Quercus xalapensis as dominant species in the HMFs of the central region of Veracruz. However, in our study Lippia myriocephala had higher structural values, which indicates that it is a secondary forest, which has been formerly subject to disturbances (González-Zamora et al, 2016).…”
Section: Discussioncontrasting
confidence: 62%
“…Both studies identified Clethra mexicana, Liquidambar styraciflua, Quercus germana and Quercus xalapensis as dominant species in the HMFs of the central region of Veracruz. However, in our study Lippia myriocephala had higher structural values, which indicates that it is a secondary forest, which has been formerly subject to disturbances (González-Zamora et al, 2016).…”
Section: Discussioncontrasting
confidence: 62%
“…Similarly, the crop type clearly affected the composition of MDC bacterial microbiome, as revealed by NMDS and PERMANOVA. Coffee samples came from perennial plantations, grown under agroforestry systems, holding several tree shade species and with minor use of fertilizers and pesticides (Gordon et al, 2007;González-Zamora et al, 2016). Moreover, tillage is not employed, leading to the establishment of many soil microbiota species (Legrand et al, 2018;Dube et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A su vez, varias de estas especies complementan su dieta con frutos y dispersan sus semillas, contribuyendo a la restauración pasiva de estos bosques tropicales húmedos (Hernández-Ladrón de Guevara et al, 2012). Adicionalmente, los bosques tropicales húmedos y semihúmedos del área de estudio están en su mayoría asociados a cafetales, por lo que mantienen condiciones estructurales y de composición similares a la de bosques primarios (Alvarez-Alvarez et al, 2020;González-Zamora et al, 2016). Esto ha permitido la presencia mayoritaria de ciertos grupos de insectívoros dependientes del sotobosque (e.g., Basileuterus belli, Dromococcyx phasianellus, Henicorhina leucophrys, Thryophilus pleurostictus) y una disminución de omnívoros y granívoros (e.g., Calocitta formosa, Columbina inca, Pitangus sulphuratus, Sporophila torqueola) que generalmente se favorecen de las modificaciones a la vegetación natural (Tejeda-Cruz y Gordon, 2008; Tejeda-Cruz y Sutherland, 2004).…”
Section: Discussionunclassified